Y-6=3(x+1)

Simple and best practice solution for Y-6=3(x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Y-6=3(x+1) equation:


Simplifying
Y + -6 = 3(x + 1)

Reorder the terms:
-6 + Y = 3(x + 1)

Reorder the terms:
-6 + Y = 3(1 + x)
-6 + Y = (1 * 3 + x * 3)
-6 + Y = (3 + 3x)

Solving
-6 + Y = 3 + 3x

Solving for variable 'Y'.

Move all terms containing Y to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + Y = 3 + 6 + 3x

Combine like terms: -6 + 6 = 0
0 + Y = 3 + 6 + 3x
Y = 3 + 6 + 3x

Combine like terms: 3 + 6 = 9
Y = 9 + 3x

Simplifying
Y = 9 + 3x

See similar equations:

| 3X+X=X+5 | | g-939/-9=5 | | 9((x^2-x)-4)+4=9(x^2-x)-4(4-(x^2-x)) | | x+4x=15000 | | 32s+600=1400 | | 10x^2-35xy-45x= | | -2-y=7 | | -9/2(-2x-4)=5 | | X+5+X=3X | | -4=8y-9+6 | | h(x)=4.2x-3 | | 3(-4c-13)=35+16c | | 13-5*7+2=-20 | | 4(c-5)-6(c+1)=7-2c | | 10x^3+6x^2+8x= | | 6x-34-3x=23 | | 3(0.75)+4(1.5)=6 | | m+3.8=5.2 | | 9(d-4)=5a-8 | | 9(w+8)+2=-3 | | g^2-14g-51=0 | | 6(k-7)=84 | | 9(w+8)+5=0 | | -12=n-7-6n | | 6x-42-20=6x | | 38+X=95 | | 11k-[4k+(-2+6k)]=0 | | 3x+4(0.75)=6 | | 95+x=38 | | 4(u-6)=2u-34 | | 0.4x+0.4(20)=0.3(x+30) | | 0.70x+0.05(2-x)=0.10(40) |

Equations solver categories